Adaptable Chinese Language Learning Card Game - Wong, Kai Kit; Goh, Bisjuin Chew Yun; Shum, See Lic; Lim, Soo Juin; Kan, Yet Jun; Lee, Chien Sing * (Asia-Pacific Society for Computers in Education, 2018)
The Chinese language is one of the world’s largest language groups. Mandarin Chinese, the primary branch of the language, is the basis for the Modern Standard Chinese language that we use today. However, it is difficult to learn. This project aims to create a game to simplify the learning process of the language and making it more fun. Based on GOMS, Schneiderman and Nielsen’s principles, a system embedded with a completing-thesentence mechanism is used to help users learn the language and appreciate its beauty. User testing results based on the Technology Acceptance model and heuristics evaluation are positive. Significance lies in the reuse of the mechanism for the learning of any language or for the enrichment/reinforcement of any subject for collaborative/competitive learning purposes.